Comparison of OSL and TL dosimetry systems against IEC and ICRP standards. (June 2023) - Zidouh, I.; Arectout, A.; Bellahsaouia, M.; Elaarabi, D.; Chamlal, H.; Maroufi, B.; Sadeq, Y.; Tazi, M.; Rodenas, J.; Boukhal, H.; Chakir, E.
Abstract: Personal and environmental radiation monitoring services are widely used through luminescent techniques. In this paper, we practiced performance testing on thermoluminescent and optically stimulated luminescent dosimeters by assessing their homogeneity, linearity, energy, and angular dependence tests. The IEC and ICRP requirements were used to compare the performance response of dosimeters. Based on the experimental results, we realized that both detectors comply with the international criteria. The homogeneity percentage was 8.9% and 13.7% for TL and OSL detectors, respectively. The percentage deviation of the linearity test does not exceed 10% for both dosimeters except for the TL dosimeters at low irradiation dose. For the angular dependence, deviations were less than 2% for TLDs and 5% for OSLDs. These detectors display mean values of the relative energy response of −15.29% and −6.51% for OSL and TL detectors. Generally, TL materials manifested low sensitivity to radiation dose levels. On the other hand, the OSLDs demonstrated a more pronounced under-response to energy beam qualities than TLDs. Regarding COV tests, TL and OSL dosimeters have passed the c2 test. Highlights: TL and OSL dosimeters characteristics were tested. Nine radiation qualities and eleven angles of incidence were used to test homogeneity, non-linearity, energy, and angular dependence. The Hp(10) measurement accuracy was evaluated by both the ICRP trumpet curve analysis and IEC 62387 covariance test.